Revocable cryptosystems from lattices - Zhang, Juanyang (2018)
In the last decade, lattices have become one of the most powerful tools in constructing cryptographic schemes, which enjoy conjectured resistance against quantum computers and strong security guarantees from worst-case to average-case reductions, as well as asymptotic efficiency. For a multi-user cryptosystem, user revocation has been a necessary but challenging problem. However, all known revocable schemes are either based on number-theoretic assumptions or lattice-based but less efficient compared to the art-of-date systems.